Slametan and Tradition in Pengakuan Pariyem: An Expression of Equality in Javanese Culture - Scarletina Vidyayani Eka; Rosana Hariyanti; Arcci Tusita (Universitas Brawijaya, 2018)
Pengakuan Pariyem is a controversial novel portraying a confession of Pariyem, a woman living in Javanese culture. Through this novel, we are able to see Javanese culture from the eyes of a Javanese woman. This paper presents an analysis on Javanese tradition, more specifically the practice of slametan in Javanese culture as it is depicted in the novel. There are ideals of life shown in Javanese culture and tradition. Slametan and the use of food in it suggest equal relations among people in Javanese culture. The equality is built to maintain the conformity to achieve harmony among these people. Even though the equality has contradictory sides, Pariyem is able to actively engage as a subject in her society and live harmoniously in it.